Water Quality Assessment of the Ancar River, Lombok Island - Imam Mauliddin; Tina Melinda; Muhamad Majdi (Jurnal Pijar MIPA, 2026)
River water quality is a parameter to determine whether the river is polluted or not. The purpose of this study is to analyze the water quality of the Ancar River located on Lombok Island, West Nusa Tenggara, based on seven main parameters, namely temperature, pH, TSS, DO, BOD, COD, and total coliform. The study employed a descriptive-qualitative approach and evaluated water quality status using the Pollution Index method, in accordance with the Decree of the Minister of Environment No. 115 of 2003. Sampling was carried out at three strategic points representing the upstream, middle, and downstream zones of the river. The data collection method used a grab sampling technique in accordance with SNI 03-7016-2004, and laboratory analysis was conducted at STTL Mataram. The test results were compared with the river water quality standards for classes I to IV under PP No. 22 of 2021. The results showed that most water quality parameters in the Ancar River remained within the quality standard thresholds, particularly temperature, pH, TSS, DO, and total coliform. However, COD values ​​at all observation points exceeded the limits for classes I–III and only met class IV, while BOD increased from upstream to downstream. These results indicate the presence of organic pollution, primarily from domestic activities and household waste, necessitating more optimal water quality management.